Ventilation and ductwork : CIBSE guide B2 : 2016. (Chartered Institution of Building Services Engineers, 2016)
Ventilation is the process by which fresh air is provided to occupants and concentrations of potentially harmful pollutants are diluted and removed from a space. It is also used to cool a space and as a mechanism to distribute thermally conditioned air for heating and cooling. It is a fundamental component of building services design since it plays a major role in the comfort, health and productivity of occupants. In addition, ventilation can contribute significantly to a building's energy load and, in some cases, can account for 50 per cent or more of total heating or cooling loss. To stem energy loss from uncontrolled air change there is growing demand for airtightness combined with demand controlled ventilation and heat recovery.